2017
DOI: 10.2147/jn.s115696
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of stem cells against spinal cord injury via regulating macrophage polarization

Abstract: Spinal cord injury (SCI) is a traumatic event that involves not just an acute physical injury but also inflammation-driven secondary injury. Macrophages play a very important role in secondary injury. The effects of macrophages on tissue damage and repair after SCI are related to macrophage polarization. Stem cell transplantation has been studied as a promising treatment for SCI. Recently, increasing evidence shows that stem cells, including mesenchymal stem, neural stem/progenitor, and embryonic stem cells, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 105 publications
1
6
0
1
Order By: Relevance
“…Using the surgically-created fetal ovine SB model, we showed that augmenting in utero surgical repair of SB defects with PMSCs can rescue neurons and cure SB-associated motor function deficits at birth [3,[9][10][11] . However, consistent with numerous other cases in which therapeutic effects were observed using MSCs, the transplanted PMSCs did not persist following transplantation, nor contribute to tissue regeneration by integration [3,[13][14][15][16][17] . Rather, the PMSCs rescued neurons via paracrine mechanisms.…”
Section: Introductionsupporting
confidence: 81%
“…Using the surgically-created fetal ovine SB model, we showed that augmenting in utero surgical repair of SB defects with PMSCs can rescue neurons and cure SB-associated motor function deficits at birth [3,[9][10][11] . However, consistent with numerous other cases in which therapeutic effects were observed using MSCs, the transplanted PMSCs did not persist following transplantation, nor contribute to tissue regeneration by integration [3,[13][14][15][16][17] . Rather, the PMSCs rescued neurons via paracrine mechanisms.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, immune-modulating characteristics of BMSCs in macrophages that contribute to tissue repair have been described, but the exact mechanisms remain to be determined 35, 36. We used a co-culture system and mainly focused on the role of MSR1 during tissue repair.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported in adult rodent brain that a portion of Iba1 þ cells are derived from infiltrated monocytes/macrophages after injury, and the I.V.-injected MSCs trapped in the spleen are capable of reducing the release of monocytes/macrophages from spleen to peripheral circulation and then to brain 43 . The study suggests that MSCs possess a remarkable immunomodulatory property 44 . The immunofluorescence results in our study showed that the expression of microglia/ macrophage marker Iba1 at the SNpc on the ipsilateral side was increased after 6-OHDA injection, whereas it was significantly decreased after MSC treatment.…”
Section: Discussionmentioning
confidence: 95%